IDENTIFIKASI DAN PEMANFAATAN TUMBUHAN OBAT DI TAMAN WISATA ALAM (TWA) KERANDANGAN - Ulfiah Fauziah; Munawir Sazali (Universitas Lambung Mangkurat, 2026)
This research aims to identify and explore the utilization of medicinal plants in the Kerandangan Nature Tourism Park (TWA) located in West Lombok, West Nusa Tenggara. Using a descriptive qualitative approach with exploratory methods, field surveys and interviews were conducted involving local community members and conservation staff. The study successfully identified 16 species of medicinal plants belonging to various families. The parts of the plants used include leaves, rhizomes, fruits, roots, flowers, and seeds. These plants are traditionally used by the local community to treat various health problems such as digestive disorders, colds, sore throats, wounds, joint pain, menstrual disorders, hypertension, and minor infections. The tropical lowland rainforest ecosystem of TWA Kerandangan provides favorable conditions for the growth and sustainability of these medicinal species. The findings indicate that TWA Kerandangan holds significant potential for the development of traditional medicine and biodiversity conservation. Furthermore, this study emphasizes the importance of documentation and preservation of ethnobotanical knowledge as part of local wisdom, which could support environmental education, community-based conservation, and sustainable economic development.